Efficacy and safety of anemoside B4 in canine pneumonia treatment: a prospective, randomized controlled trial - Ji, Jinzhao; Ding, Xiaoqing; Liu, Chuanli; Dai, Lingling; Yu, Junting; Li, Linghao; Wan, Shaobing; Song, Yangyang; Zhao, Junqing; Su, Zhetong; Jia, Kun; Li, Shoujun (Frontiers in Veterinary Science, 2025)
BackgroundCanine pneumonia is a serious respiratory disease often associated with Canine Infectious Respiratory Disease (CIRD). Current treatment strategies primarily rely on antibiotics and corticosteroids; however, the emergence of antibiotic resistance and potential side effects from prolonged corticosteroid use limit the effectiveness of these therapies in clinical practice. These challenges highlight the urgent need for alternative treatments. Anemoside B4 (AB4), derived from the traditional Chinese medicine Pulsatilla, has shown promise in preclinical studies for modulating inflammatory responses and improving clinical symptoms of pneumonia. Therefore, AB4 may offer a valuable alternative treatment option for canine pneumonia in veterinary medicine.MethodsA prospective, randomized controlled trial was conducted at the Veterinary Drug Research and Evaluation Center of South China Agricultural University. Seventy-two dogs with mild-to-moderate pneumonia were randomly assigned to one of three groups: AB4, placebo, or Chuanxinlian injection (CXL). The primary outcome was the effect of AB4 on comprehensive clinical scoring of canine pneumonia; secondary outcomes included recovery times for primary symptoms and efficacy assessments. Additionally, AB4′s safety in clinical applications was evaluated.ResultsThe AB4 group demonstrated significantly lower composite clinical scores on Days 7 and 14 compared to the placebo group (p = 0.033 and p = 0.000, respectively). Significant differences in recovery times for fever and dyspnea were observed between the AB4 and placebo groups (p = 0.041 and p = 0.024, respectively). Moreover, the cure rate and overall efficacy on Day 14 were significantly higher in the AB4 group than those in the placebo group (p = 0.001 and p = 0.009, respectively).ConclusionThese findings suggest that AB4 may be a promising treatment option for canine pneumonia, potentially serving as an alternative to traditional therapies. Further research is needed to explore its clinical potential in veterinary medicine.